2022
DOI: 10.3389/fmicb.2022.989060
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome, microbiome, and gene expression alterations in the colon of newborn piglets with intrauterine growth restriction

Abstract: Newborn animals with intrauterine growth restriction (IUGR) are characterized by impaired intestinal structure and function; however, their intestinal microbiota and metabolome profiles have not been fully identified. The present study investigated the differences in colonic microbiota, metabolomics, and barrier function-related gene expression profiles between the IUGR and normal birth weight (NBW) piglets at 7, 21, and 28 days of age. Forty-eight piglets (24 NBW and 24 IUGR) from 24 litters were assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…Phenylalanine and tyrosine metabolism are closely interconnected, with phenylalanine being metabolized into acetoacetic acid and fumaric acid via tyrosine. Previous research by Tang et al(Tang et al 2022) has also reported upregulated phenylalanine and tyrosine metabolisms in the IUGR piglet groups corroborating our ndings. Additionally, Faverzani et al(Faverzani et al 2021) highlighted the potentially detrimental effects of elevated phenylalanine levels and its keto acid derivatives, including DNA oxidative damage in glial cells.…”
supporting
confidence: 93%
“…Phenylalanine and tyrosine metabolism are closely interconnected, with phenylalanine being metabolized into acetoacetic acid and fumaric acid via tyrosine. Previous research by Tang et al(Tang et al 2022) has also reported upregulated phenylalanine and tyrosine metabolisms in the IUGR piglet groups corroborating our ndings. Additionally, Faverzani et al(Faverzani et al 2021) highlighted the potentially detrimental effects of elevated phenylalanine levels and its keto acid derivatives, including DNA oxidative damage in glial cells.…”
supporting
confidence: 93%
“…Early intestinal microbiota establishment is crucial for intestinal physiology and regulation throughout adult life. Our previous studies found significant alterations in the small intestinal and colonic microbiome and metabolome profiles of IUGR piglets during the suckling and weaning stages [ 15 , 17 ]. However, the effects of IUGR on colonic microbiota colonization and metabolism in pigs during the growing-finishing stages remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in intestinal function, microbiota composition, and metabolic activity induced by IUGR persisted throughout the life of rats [ 7 ]. Our previous studies showed that IUGR altered the colonic metabolome and microbiome in pre-weaning piglets and reduced the abundances of Firmicutes, Proteobacteria, and Lactobacillus in growing-finishing pigs [ 14 , 15 ]. In addition, IUGR decreased the colonic expressions of zonula occludens (ZO)-1 and occludin, activated nuclear factor-kappa B (NF-κB), and increased inflammatory factor levels in pre-weaning piglets [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbances in gut microbial composition have been reported in FGR piglets, 25 , 61 rats, 26 and in human neonates. 27 In our mouse model, FGR resulted in persistent fecal microbial changes into adulthood.…”
Section: Discussionmentioning
confidence: 99%